Innovative Moments in Grief Therapy: Reconstructing Meaning Following Perinatal Death - Alves, Daniela (2012)
This article presents an intensive analysis of a good outcome case of constructivist grief therapy with a bereaved mother, using the Innovative Moments Coding System (IMCS). Inspired by White and Epston’s narrative therapy, the IMCS conceptualizes therapeutic change as resulting from the elaboration and expansion of unique outcomes (or as we prefer, innovative moments), referring to experiences not predicted by the problematic or dominant self-narrative. The IMCS identifies and tracks the occurrence of 5 different types of innovative moments: action, reflection, protest, reconceptualization, and performing change. Results documented the process of meaning reconstruction over the six sessions of treatment, and demonstrated the feasibility and reliability of analyzing narrative change in this form of grief therapy, opening it to comparison with other approaches.